Projeto, implementação e análise de um inversor monofásico com saída senoidal modificada - Miotto, Lucas Gustavo da Silva (2019)
Power electronics can be considered as a science that has as objective, to apply the semiconductors devices in the conversion and control of electrical energy. These devices are used to make the conversion of power, which allows applications of six types of converters: rectifiers diodes, converters AC-DC, converters AC-AC, converters DC-DC, converters DC-AC and static switches. The inverters are power converters that transform an input DC voltage into an output AC voltage, with constant frequency and symmetric amplitude. The switching control of the inverter can be done by PWM (Pulse Width Modulation), which can be adjusted by single pulse, multiple, sinusoidal, modified sinusoidal and phase shift. In this work is presented the implementation of an inverter prototype that converts the DC input voltage to AC output voltage, which modulation is based on PWM modulation techniques with modified sinusoidal output. To perform the modulation of the electronic keys, with the purpose to present this type of output, it was used an oscillator IC IR2153. All the steps in the design of the project, as well as its theoretical basis and its results it is shown on the work.